MAKNA KONOTATIF FIGUR AYAH DALAM PUISI-PUISI INDONESIA SERTA RELEVANSINYA DALAM PENDIDIKAN KARAKTER DI SMA - Taufiq Hamdani, Muhamad; Qomariyah, U’um (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the connotative meanings attached to father figures in Indonesian poetry and analyze their relevance to strengthening character education at the senior high school level. The study is limited to four poems about father figures written by Indonesian poets and employs a descriptive qualitative approach using semiotic text analysis. The data consist of words, phrases, lines, and stanzas containing connotative meanings. The findings reveal that father figures are symbolically represented through imagery, metaphors, and poetic diction reflecting values such as hard work, responsibility, sacrifice, affection, discipline, and exemplary conduct. These values are implicitly conveyed through emotional and reflective expressions. The study also indicates that father-themed poetry is suitable as literary teaching material because it integrates students’ cognitive and affective aspects. Therefore, poetry can serve as an effective medium for contextual and meaningful character building among students.